Предпринимательское поведение: теоретико-методологические аспекты - Пачковский, Ю. (Социология: теория, методы, маркетинг, 2001)
In the article, sociological and psichological aspects of business behavior are considered as well as its mechanisms and structural components. From the theoretico-methodological point of view, three blocks of business behaviour regulation are sigled out: an "objective-situational" block, an "active-behavioral" block, and an ìinteractionalî block. In this context, bysiness behavior is determined as purposeful subjectís reactions to a definite business situation which reflects in his actions (roles, strategies, functions) guided by a certain economic interest and directed to satisfaction of actualized needs.